2013
DOI: 10.1111/1574-6976.12030
|View full text |Cite
|
Sign up to set email alerts
|

The complex microbiota of raw milk

Abstract: Here, we review what is known about the microorganisms present in raw milk, including milk from cows, sheep, goats and humans. Milk, due to its high nutritional content, can support a rich microbiota. These microorganisms enter milk from a variety of sources and, once in milk, can play a number of roles, such as facilitating dairy fermentations (e.g. Lactococcus, Lactobacillus, Streptococcus, Propionibacterium and fungal populations), causing spoilage (e.g. Pseudomonas, Clostridium, Bacillus and other spore-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
607
3
22

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 678 publications
(668 citation statements)
references
References 304 publications
(413 reference statements)
36
607
3
22
Order By: Relevance
“…Milk microbiota has also been described in rhesus monkey (26) and in other mammals such as the dairy cow (27) as well as in human breast milk samples (28)(29)(30)(31)(32)(33)(34). Our recent work using pyrosequencing demonstrated a large microbial biodiversity present in colostrum samples, with clear but mild temporal variations during the first 6 mo of breastfeeding (28).…”
Section: Breast Milk As the Link Between Mother And Infantmentioning
confidence: 72%
“…Milk microbiota has also been described in rhesus monkey (26) and in other mammals such as the dairy cow (27) as well as in human breast milk samples (28)(29)(30)(31)(32)(33)(34). Our recent work using pyrosequencing demonstrated a large microbial biodiversity present in colostrum samples, with clear but mild temporal variations during the first 6 mo of breastfeeding (28).…”
Section: Breast Milk As the Link Between Mother And Infantmentioning
confidence: 72%
“…Raw milk harbours a complex microbial community including bacteria of technological relevance such as the lactic acid bacteria (LAB), which can contribute to subsequent desirable fermentative reactions (Quigley et al 2013). Differently, a prevalent presence of spoilage bacteria can have considerable negative effects on the quality of milk and dairy products .…”
Section: Introductionmentioning
confidence: 99%
“…in the marketed raw milk. Quigley et al [3] reported that milkborne pathogens like Brucella spp. are a particular cause for concern as they are able to survive and multiply at refrigeration temperatures and may cause severe diseases.…”
Section: Districtsmentioning
confidence: 99%
“…Microorganisms enter milk from a variety of sources can be beneficial or harmful, for example Lactococcus, Lactobacillus, Streptococcus, Propionibacterium and fungal populations facilitate dairy fermentations, lactobacilli and bifidobacteria promote health while Pseudomonas, Clostridium, Bacillus and other spore-forming or thermoduric microorganisms cause spoilage and Listeria monocytogenes, Salmonella, Shiga toxin producing Escherichia coli (STEC), Campylobacter and mycotoxin-producing fungi cause disease [3]. Despite the outstanding nutritional quality and health benefits of milk, it serves also as an excellent vehicle for transmission of milkborne pathogens which may cause serious health risk to consumers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation